Ion concentration polarization on paper-based microfluidic devices and its application to preconcentrate dilute sample solutions - Yang, Ruey-Jen (Biomicrofluidics, 2015)
Microfluidic paper-based analytical devices (μPADs) are a promising solution for a wide range of point-of-care applications. The feasibility of inducing ion concentration polarization (ICP) on μPADs has thus far attracted little attention. Accordingly, this study commences by demonstrating the ICP phenomenon in a μPAD with a Nafion ion-selective membrane. We are the first to measure the current-voltage curve on a Nafion-coated μPAD in order to indicate that the ion depletion occurs and the ICP is triggered when the current reaches the limiting current. The ICP effect is then exploited to preconcentrate fluorescein on μPADs incorporating straight and convergent channels. By an optimal geometric design, it is shown that the convergent channel results in a greater preconcentration effect than the straight channel. Specifically, a 20-fold enhancement in the sample concentration is achieved after 130 s given an initial concentration of [Formula: see text] M and an external potential of 50 V. By contrast, the straight channel yields only a 10-fold improvement in the concentration after 180 s. Further, the practical feasibility of the proposed convergent-channel μPAD is demonstrated using fluorescein isothiocyanate labeled bovine serum albumin. The experimental results show that a 15-fold enhancement of the initial sample concentration ([Formula: see text] M) is obtained after 120 s given an external potential of 50 V.